Toward a formal sociology of online harassment - Cross, Katherine (Human Technology, 2019)
Online harassment and various subcategories of it, like doxing and swatting, have attracted enormous interest for several years now—and particular interest in the world of game studies in the wake of 2014’s GamerGate harassment campaign. Such protracted, crowdsourced campaigns remain undertheorized, however. Using contemporary research to modify Georg Simmel’s formal sociological method, I provide researchers and the wider public with an easily visualized structure that most harassment campaigns follow: the form of an inverted pyramid bearing down on an individual target, stratified into three orders of harassment, each defined by level of severity and invasiveness. With this form, the public can more clearly visualize online harassment as a structural rather than individual phenomenon. This form makes a significant contribution to social media research by providing an approachable theoretical framework for future studies and can also frame design interventions on harassment.